Advances in Driver Monitoring: A Review of Liveness Detection Techniques - SHOFIAH, SITI; Suartika, I Made; Hakim, M. Iman Nur; Humami, Faris; Hidayat, Dwi Wahyu; Asmoro, Langgeng (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2024)
Driver fatigue significantly contributed to traffic accidents, especially in countries with complex road characteristics like Indonesia. The research emphasized the importance of raising public awareness, developing improved detection technologies, and enforcing strict regulations. Various methods, including computer vision and physiological monitoring, were evaluated to detect driver fatigue and enhance safety through early warnings and advanced detection systems in vehicles. A systematic literature review (SLR) analyzed recent advancements, identified relevant articles, and synthesized findings to highlight current trends, gaps, and potential improvements in driver fatigue detection technology. The study found that driver monitoring systems had played a significant role in reducing traffic accidents, highlighting the importance of enhancing public awareness, advancing monitoring technologies, and enforcing strict regulations. Various methods, including computer vision and physiological monitoring, had been evaluated for their effectiveness in monitoring drivers and improving safety through early warnings and advanced detection systems in vehicles. The SLR identified current trends, gaps, and potential improvements in driver monitoring technology. Future research needed to focus on integrating various evaluation metrics, enhancing physiological monitoring techniques, optimizing overall system performance, and improving user experience. Additionally, interdisciplinary approaches and real-time data analysis and integration with existing vehicle systems were required to create more effective, efficient, and reliable driver monitoring systems, ultimately enhancing driving safety.